PHYTOCHEMICAL BIOPESTICIDES: RECENT DEVELOPMENTS AND MECHANISMS OF ACTION - Doifode, Vilas D. (International Journal of Research -GRANTHAALAYAH, 2025)
The concern over ecology and sustainable agricultural practices has led to increasing utilization of biopesticides. This chemical has proven itself to be a promising or worthy alternative to unsustainable/conventional chemicals, such as synthetic agrochemicals. These chemicals are extracted or derived from secondary metabolites belonging to plant species, offering actions that are precise, or “target specific”. It poses lower toxicity rates and provides greater scope for biodegradation, hence deeming away the perils of artificial chemicals, wherein non-degradable substances often cause hindrances in agricultural processes, like waste accumulation, rising infestation and so on. Previous research has highlighted the importance of understanding phytochemicals and the synergistic reactions they inhibit. This present study delves along similar lines to further shed light on agricultural processes that improves formulation stability and bioefficacy, with special emphasis on the utility of phytochemicals. We proceed to look at ongoing developments, mechanistic understandings and applications of our core topic, phytochemical biopesticides. We shall also be placing keen emphasis on extraction techniques, new-age technology, delivery systems and other commercial aspects of commercialization.